Different departments, different drivers: Asymmetry in antecedents and outcomes of voluntary knowledge exchange between sales and production functions. Issue 8 (7th August 2017) - Guo, Lan; Tobias, Jutta; Bendoly, Elliot; Hu, Yuming
Abstract : Purpose: The purpose of this paper is to examine the antecedents and performance consequences of voluntary information exchange between the production and sales functions. Design/methodology/approach: Building on the motivation-opportunity-ability framework, the authors first posit a general model for bilateral information exchange across functional levels. The innovation presented in this model consists in allowing both sides of such an exchange (e.g. production-to-sales and sales-to-production) to differ in the perceived adequacy of information they receive. The two sides can also differ in terms of how their motivation and ability impact that adequacy. To test the model, the authors make use of survey responses and objective data from sales, production and executive managers of 182 Chinese manufacturers. Findings: Analysis of the sample shows that the sales-to-production exchange has a smaller estimated performance effect than the production-to-sales exchange. Although shared opportunity is important in predicting both sides of the exchange, the measure of motivation appears to only significantly impact the sales-to-production exchange. In contrast, the measure of ability only appears to significantly affect the production-to-sales exchange. Research limitations/implications: Although limited to a regional context, differences in information-sharing drivers on the two sides of production-sales dyads pose strong implications that may be generalizable. Practical implications: Specifically, these findings suggest alternative approaches and foci for resource investment that higher level managers can leverage in developing more effective cross-functional work settings. Originality/value: This study differentiates itself from extant literature on information sharing by focusing on cross-functional (vs intra-functional) and voluntary (vs routine) information exchange.